GLUT1 regulates cell glycolysis and proliferation in prostate cancer. Issue 2 (6th November 2017) - Xiao, Hengjun; Wang, Jun; Yan, Weixin; Cui, Yubin; Chen, Zheng; Gao, Xin; Wen, Xingqiao; Chen, Jun
Abstract : Background: Glucose transporter 1 (GLUT1) plays a critical role in tumorigenesis and tumor progression in multiple cancer types. However, the specific function and clinical significance of GLUT1 in prostate cancer (PCa) are still unclear. Therefore, in this study, we investigated the role of GLUT1 in PCa. Methods: GLUT1 protein levels in prostate cancer tissue and tumor‐adjacent normal tissues were measured and compared. Furthermore, real‐time PCR and Western blot analysis were both used to detect GLUT1 expression levels in different PCa cell lines. Flow cytometry and cell‐based assays, such as a glucose uptake and lactate secretion assay, CCK‐8 assay, and transwell migration and wound healing assay, were used to monitor cancer cell cycle distribution, glycolysis, proliferation, and motility, respectively. Moreover, a mouse tumor xenograft model was used to investigate the role of GLUT1 in tumor progression in vivo. Results: GLUT1 expression levels are higher in PCa tissues than in tumor‐adjacent normal tissues. The results from real‐time PCR and Western blot analysis revealed a similar increase in the GLUT1 expression levels in PCa cell lines. Moreover, knockdown of GLUT1 inhibits cell glycolysis and proliferation and leads to cell cycle arrest at G2/M phase in the 22RV1 cell line but not in the PC3 cell line. In vivo experiments further confirmed that GLUT1 knockdown inhibits the growth of tumors derived from the 22RV1 cell line. In addition, we also showed that GLUT1 knockdown has no effect on cell migration in vitro. Conclusions: GLUT1 may play an important role in PCa progression via mediating glycolysis and proliferation. Our study also indicated a potential crosstalk between GLUT1‐mediated glycolysis and androgen sensitivity in PCa.